Physiological markers of training responses in elite Paralympic swimmers - Edmonds, R. (University of the Sunshine Coast, 2017)
The aim of this research project was to examine the effectiveness of heart rate variability (HRV), salivary immunoglobulin A (sIgA) and salivary alpha amylase (sAA) as practical markers to measure training responses in elite athletes. The chronic and acute training responses of Paralympic swimmers were analysed during their various training phases and at international competition including the Paralympic Games. Daily and weekly HRV analysis was assessed, with weekly measures of sIgA and sAA incorporated to examine training responses during periodised training. To classify the training responses in elite athletes, minimal fluctuations in HRV were identified during periodised training, with the weekly average for HRV similar to daily values during a normal training week. This result clarified that daily analysis of HRV was not required during seasonal training (i.e. non-taper). However, the analysis of HRV during a taper training phase established significant trends in cardiac autonomic activity, indicative of a readiness to perform. By monitoring the weekly responses of HRV, sIgA and sAA over a typical training cycle, it was observed that well periodised training maintained these indices within normal baseline values. The impact of high level competition, however, created significant depressions in HRV coupled with an increase in sAA. These results indicated that elite level competition impacts autonomic balance for at least two days. As such, implementation of appropriate recovery methods and rest periods is advised to alleviate the accumulated stress following competition. Examining the acute stress responses of HRV, sIgA and sAA, it was identified that these physiological markers respond consistently to a high intensity training session, likely an effect of well managed training and recovery prescription during seasonal training.